DOCÊNCIA NA EXTENSÃO UNIVERSITÁRIA: FORMAÇÃO-ORGANIZAÇÃO DO TRABALHO ASSOCIADO NO MOVIMENTO DE ASSOCIAÇÕES E COOPERATIVAS SOLIDÁRIAS - Zart, Laudemir Luiz; Bitencourt, Loriége Pessoa; Ribeiro, Cristiane Gonçalves; Souza, Maria José Dantas (Revista Didática Sistêmica, 2026)
This Pedagogical Charter presents and reflects on the theme of organizational formation in the economic and cultural field of solidarity-based cooperativism, grounded in the theory of associated work. The activities are university extension programs that connect the university with an institutionalized social entity managed by peasants. The dialogical and problematizing relationships are based on the theory of the social production of knowledge, substantiated in the epistemological and gnoseological frameworks of Paulo Freire. The methodology is research-based training, which involves educational and investigative processes for the socialization of historical-social knowledge and the configuration of innovative knowledge of social practices and technologies in the organization of socio-productive groups in the institution, management, and development of solidarity cooperatives. The results are socialized knowledge and the acquisition of new knowledge in human formation processes for the sociological and philosophical understanding of organizational experiences and the development of planning, administrative, management, and evaluation skills in associated work organizations.